2015
DOI: 10.5694/mja14.00701
|View full text |Cite
|
Sign up to set email alerts
|

Are Aboriginal people more likely to be diagnosed with more advanced cancer?

Abstract: Aboriginal people were more likely than non-Aboriginal people to be diagnosed with more advanced cancer for only a few cancer types, most notably head and neck cancers. Differences in spread of disease at diagnosis are unlikely to explain much of the survival differences observed across a wide range of cancers between Aboriginal and non-Aboriginal people in NSW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Kelly et al 47 found that fewer crcs diagnosed in Alaska Native people were localized (30% vs. 38% in white U.S. patients), which could be related to lower screening rates; however, the percentages of individuals diagnosed with regional or distant-stage crc were more similar. In contrast, Gibberd et al 49 found no significant difference in stage at diagnosis for Australian Aboriginal people compared with non-Aboriginal people diagnosed with bca or crc.…”
Section: Discussionmentioning
confidence: 84%
“…Kelly et al 47 found that fewer crcs diagnosed in Alaska Native people were localized (30% vs. 38% in white U.S. patients), which could be related to lower screening rates; however, the percentages of individuals diagnosed with regional or distant-stage crc were more similar. In contrast, Gibberd et al 49 found no significant difference in stage at diagnosis for Australian Aboriginal people compared with non-Aboriginal people diagnosed with bca or crc.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have similarly reported that Aboriginal peoples had more advanced stage [4–6, 20] but to our knowledge only one previous study in addition to ours has systematically examined cancer site-specific differences [19]. Age-stratified analyses indicated that the association between Aboriginal status and advanced stage tended to be stronger in younger age groups, however, interaction was not statistically significant.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, available data indicate that Aboriginal peoples have a higher incidence of cancers with a poorer prognosis, reflecting differences in risk factor prevalence [17, 18]. Compared with non-Aboriginal people, Aboriginal peoples were more likely to be diagnosed with advanced stages for head and neck cancers [19], colon/rectum, breast, and cervix cancers, and non-Hodgkin lymphoma but not lung cancer [20]. Some studies have found lower survival among Aboriginal than non-Aboriginal people, even after adjustment for stage [4, 6, 9, 20], whereas other studies have indicated that the survival gap narrowed and became non-significant after adjustment for stage and other clinical factors [16] or after adjustment for comorbidities, socioeconomic disadvantage and remoteness [5].…”
Section: Introductionmentioning
confidence: 99%
“…“Between 2008 and 2012, Indigenous Australians were 1.3 times more likely to die from all cancers combined than non-Indigenous Australians” (Australian Institute of Health and Welfare [AIHW] & Australasian Association of Cancer Registries, 2014, p. 21). This is partly because Aboriginal and Torres Strait Islander peoples are more likely to be diagnosed with more advanced cancers—and particularly cancers with higher mortality rates (AIHW & Australasian Association of Cancer Registries, 2014; Gibberd, Supramaniam, Dillon, Armstrong, & O’Connell, 2015). …”
mentioning
confidence: 99%